2012
DOI: 10.1172/jci60144
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear protein 1 promotes pancreatic cancer development and protects cells from stress by inhibiting apoptosis

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has the lowest survival rate of all cancers and shows remarkable resistance to cell stress. Nuclear protein 1 (Nupr1), which mediates stress response in the pancreas, is frequently upregulated in pancreatic cancer. Here, we report that Nupr1 plays an essential role in pancreatic tumorigenesis. In a mouse model of pancreatic cancer with constitutively expressed oncogenic Kras G12D , we found that loss of Nupr1 protected from the development of pancreatic intraepithelial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
130
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 51 publications
3
130
0
Order By: Relevance
“…Therefore, due to their ability to regulate gene expression processes that determine cellular patterns of morphogenesis, Polycomb complexes are key regulators of cell development, maintain tissue homeostasis, and, when altered, give rise to cancer. NUPR1 plays a major role in pancreatic ductal adenocarcinoma (PDAC), because the oncogenic Kras G12D expression in the mouse pancreas is unable to promote precancerous lesions in the absence of NUPR1 expression (31,32,35). In addition, RING1B is weakly expressed in pancreatic intraepithelial neoplasias but strongly expressed in PDAC [as well as in hepatocellular carcinoma (14)].…”
Section: Structural Determinants Of the C-ring1b/nupr1 Interaction Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, due to their ability to regulate gene expression processes that determine cellular patterns of morphogenesis, Polycomb complexes are key regulators of cell development, maintain tissue homeostasis, and, when altered, give rise to cancer. NUPR1 plays a major role in pancreatic ductal adenocarcinoma (PDAC), because the oncogenic Kras G12D expression in the mouse pancreas is unable to promote precancerous lesions in the absence of NUPR1 expression (31,32,35). In addition, RING1B is weakly expressed in pancreatic intraepithelial neoplasias but strongly expressed in PDAC [as well as in hepatocellular carcinoma (14)].…”
Section: Structural Determinants Of the C-ring1b/nupr1 Interaction Inmentioning
confidence: 99%
“…Indeed, NUPR1 participates in the regulation of apoptosis by forming a complex with another IDP, prothymosin α (33), as well as being involved in DNA repair (34). In addition, NUPR1 plays key roles in pancreatic tumorigenesis, acting downstream of the Kras G12D oncogenes, which are critical for pancreatic carcinogenesis (35). Therefore, given the similarities in the physicochemical properties of RYBP and NUPR1 (namely, high isoelectric point, DNAbinding features, and an intrinsic disordered state), and the involvement of C-RING1B in some types of cancer, we hypothesize that this domain might also bind to NUPR1.…”
mentioning
confidence: 99%
“…9 P8 participates in a wide range of biological functions in tumorigenesis, including anti-inflammatory, 10 cell cycle regulation, 11 autophagy, 12 and apoptosis inhibition. 13 Accumulating studies have shown that p8 is overexpressed in various cancer cells including pancreatic cancer, 14 colorectal carcinoma 15 and brain tumors. 16 Moreover, it has been reported that p8 is involved in the resistance of cancer cells to gemcitabine and adriamycin.…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic and epigenetic factors (regulating senescence, autophagy, cell cycle, and apoptosis) may positively or negatively modulate the transforming activity of mutant KRAS in pancreatic cells, thereby modulating PanIN development. Among these factors, we recently described a novel intracellular pathway essential for KRAS transforming activity in the pancreas controlled by the pancreatitis-activated protein NUPR1 (also known as p8 or COM1), which involved RELB, but not RELA (6). We demonstrated that genetic deletion of Nupr1 in mice inhibits Kras-dependent PanIN development in a Relbdependent manner.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, pancreatic-specific deletion of Relb in a Kras G12D background resulted in delayed PanIN development. In addition, we found that disruption of this novel NUPR1-RELB transcriptional pathway affects the expression of genes encoding proteins that can serve as effectors of their function, such as immediate early response 3 (IER3) (6). Thus, efficient PanIN formation is dependent on Nupr1 and Relb expression, with likely involvement of Ier3.…”
Section: Introductionmentioning
confidence: 99%